Islamic Moderation and the Sustainable Development Goals: Conceptual Foundations and Indonesian Contextual Realizations - Iffatin Nur; Indri Hadisiswati; Hiba Fajarwati; Haniefa Nuruddienil Fithriy; Muhammad Thufaili Ubaidillah (Journal of Sustainability Perspectives, 2026)
This article examines the significance of Islamic moderation (wasaṭiyyah) in supporting Indonesia’s efforts to achieve the Sustainable Development Goals (SDGs). Employing a qualitative, interpretive design, the study integrates an integrative literature review of classical and contemporary scholarship with systematic document analysis and thematic content analysis of key institutional reports. Drawing upon classical Islamic scholarship, contemporary Indonesian religious thought, and empirical examples across Islamic institutions, the study demonstrates that moderation, embodied by organizations like Nahdlatul Ulama (NU) and Muhammadiyah, provides a culturally grounded framework for advancing inclusive development, contributing directly to SDGs related to poverty alleviation, quality education, gender equality, climate action, and peacebuilding. However, the study also identifies complex challenges, including political polarization, digital radicalization, institutional fragmentation, and resource disparities, that constrain its effectiveness. The article concludes that enhancing policy coordination, expanding religious literacy, and empowering community leaders are essential for maximizing moderation’s role in Indonesia’s pursuit of the SDGs. Future research should empirically quantify the impact of specific faith-based initiatives on SDG indicators and comparatively analyze the Indonesian model of moderation with other Muslim-majority contexts to assess its broader applicability.